Peripheral Inflammatory Factors and Acute Myocardial Infarction Risk: A Mendelian Randomization Study - Yaxi Chen; Ling Zeng (Ubiquity Press, 2023)
Background: Previous observational studies have confirmed the relationship between inflammation and acute myocardial infarction (AMI), but genetic evidence is still lacking. The aim of this study was to explore the bidirectional association of multiple peripheral inflammatory factors with this disease at the genetic level. Methods: Summary data for AMI and several peripheral inflammatory factors (such as interleukin-10 and interleukin-18) were collected from published genome-wide correlation studies. Based on the correlation, independence, and exclusivity assumptions, a total of 9 to 110 instrumental variables were selected from these summary data to predict the above traits. Two-sample Mendelian randomization methods, including inverse-variance weighted (IVW), were used to make causal inferences between exposures and outcomes. Sensitivity analyses including Cochran's Q, MR-Egger intercept, leave-one-out, forest plot, and MR-PRESSO were adopted to assess heterogeneity and horizontal pleiotropy. Results: The IVW reported that elevated peripheral levels of interleukin-10 and interleukin-18 were nominally associated with a reduced risk of AMI (OR = 0.876, 95% CI = 0.788 ~ 0.974, P = 0.015; OR = 0.934, 95% CI = 0.875 ~ 0.997, P = 0.040). The IVW also reported that the risk of AMI nominally increased the peripheral level of interleukin-10 (OR = 1.062, 95% CI = 1.003 ~ 1.124, P = 0.040). No significant heterogeneity or horizontal pleiotropy were found by sensitivity analyses. Conclusion: Both interleukin-10 and interleukin-18 were peripheral inflammatory factors genetically associated with AMI. In particular, combined with previous knowledge, interleukin-10 may have a protective effect on the onset, progression, and prognosis of the disease.